2019
DOI: 10.2308/acch-52349
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fraud Risk Assessment Frequency and Fraud Inquiry Timing on Auditors' Skeptical Judgments and Actions

Abstract: SYNOPSIS Identifying ways to improve and maintain professional skepticism, particularly for the purpose of reducing the risk of material misstatement due to fraud, continues to be a top priority for the auditing profession. This study examines two strategies for improving skeptical behavior in a fraud-related task: (1) practicing inward-directed skepticism through repeated risk assessments and (2) performing timely fraud inquiries of operational-level employees. Results indicate auditors made mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…Mereka mengandalkan hubungan antara kelemahan pengendalian internal dan kesalahan akuntansi sebagai dasar judgement auditor (Frederick & Libby, 1986). Auditor disarankan untuk meninjau perikatan audit lebih dari sekali untuk mempertahankan skeptisisme dan mengurangi bias (Brasel et al, 2019). Beberapa faktor seperti kepentingan yang bertentangan, batasan dalam komunikasi, dan motivasi pribadi, berkontribusi untuk meyakinkan judgement auditor (Carpenter & Dirsmith, 1993), dan itu menegaskan bahwa kesamaan tujuan antara atasan dan bawahan dapat meningkatkan judgement auditor (Asare & Wright, 2001).…”
Section: Telaah Literaturunclassified
See 1 more Smart Citation
“…Mereka mengandalkan hubungan antara kelemahan pengendalian internal dan kesalahan akuntansi sebagai dasar judgement auditor (Frederick & Libby, 1986). Auditor disarankan untuk meninjau perikatan audit lebih dari sekali untuk mempertahankan skeptisisme dan mengurangi bias (Brasel et al, 2019). Beberapa faktor seperti kepentingan yang bertentangan, batasan dalam komunikasi, dan motivasi pribadi, berkontribusi untuk meyakinkan judgement auditor (Carpenter & Dirsmith, 1993), dan itu menegaskan bahwa kesamaan tujuan antara atasan dan bawahan dapat meningkatkan judgement auditor (Asare & Wright, 2001).…”
Section: Telaah Literaturunclassified
“…Beberapa faktor seperti kepentingan yang bertentangan, batasan dalam komunikasi, dan motivasi pribadi, berkontribusi untuk meyakinkan judgement auditor (Carpenter & Dirsmith, 1993), dan itu menegaskan bahwa kesamaan tujuan antara atasan dan bawahan dapat meningkatkan judgement auditor (Asare & Wright, 2001). Penelitian lain mencakup bahwa auditor yang tidak mudah percaya menunjukkan kecenderungan untuk mengubah judgement sebagai bentuk aksi dalam menerapkan sikap skeptis (Brasel et al, 2019). Pembahasan di atas menunjukkan bahwa telah banyak penelitian tentang auditor judgement.…”
Section: Telaah Literaturunclassified
“…Prior audit research finds that higher trait skeptics exhibit behaviors consistent with the three dimensions (e.g., Brasel et al, 2019;Eutsler et al, 2018;Koch et al, 2016;Quadackers et al, 2014). For example, survey research finds that auditors higher on the Hurtt (2010) trait skepticism scale engage in greater searching for evidence, questioning of evidence, and suspension of judgment when performing audit tasks (Janssen et al, 2021).…”
Section: Auditors' Skeptical Versus Client Service Dispositionsmentioning
confidence: 99%
“…Furthermore, several studies suggest that determining the critical risk factors could help auditors in an audit case and fraud risk assessment and affect the nature, timing, and extent of the audit procedures, evidence collected, and audit quality (Colbert, 1996;Helliar et al, 1996;Bedard et al, 1999;Blay et al 2007;De Martinis et al, 2007;Blay et al, 2008;Chang et al, 2008;Razak et al, 2018). Brasel et al (2019) found that auditors made more skeptical judgments when revisiting and reassessing fraud risk assessments. Furthermore, when auditors perform operational-level fraud inquiries before substantive testing, they exhibit a significantly greater skeptical judgment than when inquiries are performed subsequently or not at all.…”
Section: Literature Reviewmentioning
confidence: 99%